Transformasi Digital dalam Era Society 5.0: Peluang dan Tantangan bagi Start-Up Berbasis Teknologi - Yasmin, Nabilla; Jhon Veri (Indo-MathEdu Intellectuals Journal, 2025)
Digital transformation is a key driver in realizing a technology-based society as envisioned in the concept of Society 5.0. In this context, technology-based start-ups play a strategic role as agents of social innovation and the digital economy. This study aims to systematically examine the opportunities and challenges of digital transformation faced by start-ups in the era of Society 5.0. The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 framework, involving 68 scientific articles published between 2018 and 2025. Data were collected from leading databases such as Scopus, IEEE Xplore, ScienceDirect, and Google Scholar, and analyzed using thematic content analysis and bibliometric analysis with the support of VOSviewer software. The findings reveal that start-ups have significant potential to accelerate social transformation through services based on AI, IoT, and Big Data. However, they also face major challenges such as low digital literacy, infrastructure limitations, unadaptive regulations, and technological access gaps. Common strategies adopted include digital reinvention, strengthening digital human capital, and fostering cross-sector collaboration. This study contributes to a deeper understanding of digital transformation dynamics in the Start-up sector and serves as a strategic reference for policymakers, academics, and industry practitioners.